Marine algae of St. Martins Island, Bangladesh. VII. Acrochaetium nurulislamii sp. nov. and new records of Acrochaetium (Rhodophyceae) - Aziz, Abdul; Islam, Shahima (Bangladesh Journal of Botany, 2010)
Acrochaetium nurulislamii sp. nov. and Acrochaetium polysporum Howe, A. sagraeanum (Montagne) Bornet and A. zosterae Papenfuss are recorded and described for the first time from the St. Martin's Island, Cox's Bazar, Bangladesh. Key words: Acrochaetium nurulislamii sp. nov.; Acrochaetium spp.; Red algae; Bangladesh DOI: 10.3329/bjb.v38i2.5139 Bangladesh J. Bot. 38(2): 145-151, 2009 (December)